The implementation of Alu insertion polymorphism as a genetic marker for forensic investigation in a Jordanian population sample - Zainab A., Al-Mazaydeh; Salem R., Yasin; Lubna H., Tahtamouni (African Science Publications, 2020)
Alu element is one of the most abundant short interspersed nuclear elements (SINE) in the human genome with great forensic potential. The current study focused on the analysis of the utility of Alu insertion polymorphism in forensic DNA typing in a Jordanian population sample (central Jordan). Alu insertions in seven different genetic loci were amplified using Polymerase Chain Reaction (PCR). The frequencies of the Alu insertions were 0.345 for ACE, 0.441 for TPA25, 0.291 for PV92, 0.845 for APO, 0.468 for FXIIIB, 0.727 for HS3.23 and 0.527 for B65. APO and FXIIIB Alu insertions were the most dominant alleles, while PV92 Alu insertion was the least frequent. Combined Power of Discrimination (PD) for those seven loci was 0.998285646, whereas the combined Power of Exclusion (PE) was 0.4987.Combining the seven Alu insertion/deletion data along with the Jordanian combined STR data should give an exceptional resolution power between Jordanian individuals.
Keywords: Forensic science, Alu polymorphism, Allelic frequency, Jordanians